A New Species of Trigonostemon Blume from the Khasi Hills - Deb, D. B.; Deka, G. K. (Indian Forester, 1965)
Trigonostemon chatterjii Deb et Oeka spec. nov. (Family Euphorbiaceae-Tribe Cratoneae - sect. Trigonostemon) is described with illustrations. This plant was collected by Shri G.K. Deka from the Khasi Hills, Assam, India. The late Dr. D. Chatterjee examined the specimen at Kew, England and considered it to be a new species. The specific epithet is given in his honour.